A Coffee Shop Marketing Strategy Analysis Using STP and the Ansoff Matrix: A Systematic Literature Review - Rani Mahadika Gumanti (Al-Kharaj: Journal of Islamic Economic and Business, 2025)
This study aims to analyze coffee shop marketing strategies by integrating the Segmentation, Targeting, and Positioning (STP) framework with the Ansoff Matrix as a conceptual approach to formulate growth strategies and strengthen competitive positioning. The research employs a qualitative approach using a Systematic Literature Review (SLR) based on the PRISMA protocol, through the review of over 300 international and national scholarly articles, which were then filtered down to 48 articles relevant to the research topic. The findings indicate that the application of STP plays a crucial role in understanding consumer characteristics, selecting appropriate target markets, and establishing a strong brand position. Meanwhile, the Ansoff Matrix provides strategic guidance for directing business growth through four alternatives: market penetration, product development, market development, and diversification. The integration of these two frameworks produces a comprehensive, long-term-oriented marketing strategy, enabling coffee shops to enhance competitiveness, expand market reach, and create sustainable added value. The study concludes that the synergy between STP and the Ansoff Matrix can serve as an effective conceptual guide for coffee shop entrepreneurs in designing marketing strategies that are adaptive to changes in consumer behavior and industry dynamics.